The climate policy narrative for a dangerously warming world - Sanford, Todd; Frumhoff, Peter C.; Luers, Amy; Gulledge, Jay (Nature Climate Change, 2014)
It is time to acknowledge that global average temperatures are likely to rise above the 2 °C policy target and consider how that deeply troubling prospect should affect priorities for communicating and managing the risks of a dangerously warming climate.